EFL Students' Perception on the Use of Social Media Platforms as Learning Tools - Joko Prayudha (Program Studi Pendidikan Bahasa Inggris, FKIP - Universitas Iskandar Muda, 2022)
The Covid-19 pandemic has spread to all parts of the world including Indonesia. The existence of the Covid 19 problem has changed many aspects of human life, including in the field of education. Therefore, the use of social media devices has become an alternative learning tool in providing material to students during the Covid-19 pandemic. With this new challenge, every human being is challenged to change old habits into new ones, especially in the world of education. This study aims at determining the EFL students' perceptions regarding the use of various social media tools to support online learning during the Covid-19 pandemic. The method used in this research was qualitative using a descriptive approach. The sampling technique used in this study was random sampling by distributing questionnaires via google form and conducting interviews with 25 selected students to explore students' perceptions about the use of social media in English learning. The data that has been collected is analyzed in an elaborated way. In the application of learning using social media, there are many positive responses given by students, but there are also students who experience some problems in the application of learning using social media. Even among them, they also experience various difficulties in using it, especially in internet access. The results show that the use of social media platforms provides several advantages in its implementation, such as the flexibility of time, the effectiveness of its use, ease, interactive, fun use. However, the challenges are very monotonous learning activities, spending quotas, boredom and difficulty expressing their creativity, bad responses and an erratic schedule.